1994
DOI: 10.1088/0953-2048/7/9/012
|View full text |Cite
|
Sign up to set email alerts
|

Glass coating of YBa2Cu3Oxwires

Abstract: PbO/B203-based glass coatings were applied to monolithic YBa2Cu30x wires. Smooth, dense coatings were obtained by heating in O2 at 375 "C for 0.5-1.0 h. The coatings did not affect superconducting properties and provided mechanical strengthening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…12,18,19 Although Y-123 is greatly degraded by water and humid air, 9,20 this effect should not preclude its practical application since it is possible to protect Y-123 by coating of silver or glass. [21][22][23][24][25] Although most of the literature reports are focusing on the reaction of high-T c superconductors with water or vapor qualitatively, 11,16,17 we have investigated the reaction of Bi-2223 with water kinetically. 14,15 It is found that the rate law is first order dependent on the surface area of the powder sample, and the reaction rate is greatly reduced at high pH.…”
Section: Introductionmentioning
confidence: 99%
“…12,18,19 Although Y-123 is greatly degraded by water and humid air, 9,20 this effect should not preclude its practical application since it is possible to protect Y-123 by coating of silver or glass. [21][22][23][24][25] Although most of the literature reports are focusing on the reaction of high-T c superconductors with water or vapor qualitatively, 11,16,17 we have investigated the reaction of Bi-2223 with water kinetically. 14,15 It is found that the rate law is first order dependent on the surface area of the powder sample, and the reaction rate is greatly reduced at high pH.…”
Section: Introductionmentioning
confidence: 99%